(untitled) (Siddhajyoti Interdisciplinary Journal, 2025)
This article explores how the first author (Hem), changed from being a traditional teacher who focused solely on abstract math concepts to becoming a critical and culturally aware mathematics teacher in Nepal. The paper is written from the viewpoint of the author’s personal experiences, using the first-person perspective "I". The purpose of this study is to critically discover my de/contextualized learning and teaching of mathematics to visualize myself as a transformative learner and teacher of mathematics. This study is framed through the research question: How have I been developing myself as a contextualized learner and teacher from traditional learner and teacher of mathematics? During my academic journey, I have tackled many mathematics problems and faced numerous classroom challenges. Over time, I have changed my approach from just solving math problems to teaching in a way that relates to real life. I have spent more than ten years refining how I teach, with the goal of helping students do better in exams. At this moment, I am navigating a critical point and actively searching for more effective alternatives to enhance culturally meaningful learning of mathematics for students through a shift toward transformation.